Geophagia and risk of squamous cell esophageal cancer in the African esophageal cancer corridor: Findings from the ESCCAPE multicountry case‐control studies. Issue 6 (28th May 2021) - Narh, Clement T.; Dzamalala, Charles P.; Mmbaga, Blandina T.; Menya, Diana; Mlombe, Yohannie; Finch, Peter; Nyakunga, Gissela; Schüz, Joachim; McCormack, Valerie; ,
Abstract: Geophagia, the intentional practice of consuming soil, occurs across the African esophageal cancer corridor, particularly during pregnancy. We investigated whether this practice is linked to endemic esophageal squamous cell carcinoma (ESCC) in this region. We conducted ESCC case‐control studies in Tanzania, Malawi and Kenya. Cases were patients with incident histologically/clinically confirmed ESCC and controls were hospital patients/visitors without digestive diseases. Participants were asked if they had ever eaten soil (never/regularly/pregnancy‐only). Odds ratios (OR) are adjusted for sex, age, tobacco, alcohol, country, religion and marital status. Overall, 934 cases (Malawi 535, Tanzania 304 and Kenya females 95) and 995 controls provided geophagia information. Among controls, ever‐geophagia was common in women (Malawi 49%, Kenya 43% and Tanzania 29%) but not in men (10% Malawi, <1% Tanzania). In women, ESCC ORs were 1.25 (95% CI: 0.70, 2.22) for regular versus never geophagia and 0.88 (95% CI: 0.64, 1.22) for pregnancy‐only versus never. Findings were stronger based on comparisons of cases with hospital visitor controls and were null using hospital patients as controls. In conclusion, geophagia is too rare to contribute to the male ESCC burden in Africa. In women, the practice is common but we did not find consistent evidence of a link to ESCC. The study cannot rule out selection bias masking modest effects. Physical effects of geophagia do not appear to have a large impact on overall ESCC risk. Research with improved constituent‐based geophagia exposure assessment is needed.